(untitled) (Research, Society and Development, 2020)
Ameloblastoma is a benign odontogenic tumor of epithelial origin with slow, asymptomatic, rare growth and is associated with a high rate of recurrence, being responsible for 1% of mandibular tumors. There are several variations of these tumors, with solid / multicystic and unicystic types being the most recurrent. The signs are discrete and rarely noticed by the patient in the early stages. In the imaging examination, it presents itself as a well-delimited radiolucent image, which may be associated with the crown of an unerupted tooth, resorption of adjacent roots and vestibular-lingual medullary expansion. In the literature, the most appropriate treatment for the management of such pathology is still controversial, since there are conservative philosophies such as curettage, marsupialization (decompression) and defending currents of the radical surgical approach through resection with a safety margin. This study aims to report a case of curettage of follicular unicystic ameloblastoma with a single incidence of recurrence and treated again by means of a conservative surgical approach and continuing with a 19-year clinical preservation, without any clinical or imaging signs of recurrence.